Nursing of a peritoneal dialysis patient with severe edema complicated with heart failure (1例腹膜透析患者重度水肿合并心力衰竭的护理体会) - ZHOU Gexia (周革霞); LI Qian (李倩); ZHAO Jing (赵静); LI Yanshuang (李艳爽); CAI Zhen (蔡朕); ZHAO Yan (赵妍); ZHAO Dingyan (赵丁燕); LIU Liheng (刘丽姮) (中西医结合护理)
This paper summarized the nursing measures for a peritoneal dialysis patient with severe edema complicated with heart failure. The integrated treatment of nephropathy was used to relieve the fluid overload. Comprehensive nursing interventions such as dietary guidance, enhancing the patient’s awareness and practice of peritoneal dialysis were carried out. In addition, Traditional Chinese Medicine (TCM) nursing technology including TCM enema, Chinese herbal medicine penetration, five-element music therapy were performed to improve the recovery of the patient. (本文总结1例腹膜透析患者重度水肿合并心力衰竭的护理经验, 通过肾病一体化治疗方案改善患者容量超负荷症状, 同时开展饮食干预、加强腹膜透析相关理论知识与操作的培训并联合中药灌肠、中药超声透药、五行音乐等中医护理特色技术, 有助于促进患者康复。)